A New Mobile Application for Standardizing Diabetic Foot Images. (January 2018) - Yap, Moi Hoon; Chatwin, Katie E.; Ng, Choon-Ching; Abbott, Caroline A.; Bowling, Frank L.; Rajbhandari, Satyan; Boulton, Andrew J. M.; Reeves, Neil D.
Background: We describe the development of a new mobile app called "FootSnap, " to standardize photographs of diabetic feet and test its reliability on different occasions and between different operators. Methods: FootSnap was developed by a multidisciplinary team for use with the iPad. The plantar surface of 30 diabetic feet and 30 nondiabetic control feet were imaged using FootSnap on two separate occasions by two different operators. Reproducibility of foot images was determined using the Jaccard similarity index (JSI). Results: High intra- and interoperator reliability was demonstrated with JSI values of 0.89-0.91 for diabetic feet and 0.93-0.94 for control feet. Conclusions: Similarly high reliability between groups indicates FootSnap is appropriate for longitudinal follow-ups in diabetic feet, with potential for monitoring pathology.